Características morfofisiológicas ruminais, alterações hepáticas e perfil de ácidos graxos da carne de ovinos alimentados com dietas contendo diferentes teores de óleo residual de fritura - Teófilo, Tiago da Silva (Universidade Federal Rural do Semi-Árido, 2020)
The use of alternative products in the feeding of ruminants can have beneficial characteristics, both from an economic and environmental point of view. Supplementation of sheep with residual frying oil (RFO), as a strategy to increase the dietary energy supply can modulate the characteristics of ruminal morphophysiology, as well as of the hepatic metabolism and meat of such animals. Thus, the objective was to evaluate the morphophysiological characteristics of the rumen, as well as possible hepatic changes and the fatty acid profile of the meat of finishing sheep fed with different levels of RFO. For this, 24 male sheep, with no defined racial pattern, were distributed in a completely randomized design with four treatments (six rams per treatment). The rams were kept on pasture from birth up to 120 days and then confined for 60 days, where they were submitted to one of the experimental diets, which consisted of different levels of inclusion of RFO in the diet (0, 3, 6 and 9%) with based on dry matter. RFO supplementation did not influence int the thickness of the epithelium and in the mitotic index. However, rams supplemented with 9% of RFO had a reduced papillae size. The dietary increment of the RFO (6 and 9%) provided an increase in the times of reduction of the methylene blue, sedimentation and flotation in the ruminal fluid. The addition of RFO supplementation promoted an increase in microscopic hepatic lesions, accompanied by a reduction in glycogen deposition in the hepatic parenchyma. The meat of rams fed with 9% oil inclusion showed lower values of oleic acid (C18:1), when compared with the control group. The rams in the control group showed a lower value of α-linolenic acid (C18:3), when compared with the other groups. There were no differences in thrombogenic and atherogenic indices. The inclusion of residual frying oil at high levels can generate changes in the fermentation patterns, as well as in the ruminal mucosa and hepatic parenchyma, however, not reflecting in substantial changes in the fatty acid profile of the meat of the rams, constituting an alternative for the use of this residue from the food industry, as long as the inclusion limits are respected
Keywords: Lipídios; Nutrição de ruminantes; Alterações patológicas; Alimentos alternativos; Lipids; Ruminant Nutrition; Pathological changes; Alternative foods; CIENCIAS AGRARIAS::MEDICINA VETERINARIA